The game plan - Mayhem Pictures (Firm); Walt Disney Pictures (Burbank, CA Walt Disney Home Entertainment Distributed by Walt Disney Studios Home Entertainment, 2008)
Superstar quarterback Joe Kingman has an ego bigger than a football field. Joe is getting ready for a run at the big championship game when the 8-year-old daughter he never knew existed shows up at his not-so-family-friendly bachelor pad. As the big game gets closer, he begins to realize the most meaningful win he can achieve is the heart of the one little fan who counts the most
Title from container
1
Keywords: Fathers and daughters $z United States $v Drama; Football teams $z United States $v Drama; Quarterbacks (Football) -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs